2018
DOI: 10.1016/j.jacc.2018.03.539
|View full text |Cite
|
Sign up to set email alerts
|

Angioscopic Evaluation of Spontaneously Ruptured Aortic Plaques

Abstract: SRAP are commonly scattered, and their dimensions were smaller than previously recognized. (Detecting Ruptured Aortic Plaques by Nonobstructive Angioscopy; UMIN000029772).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
97
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(98 citation statements)
references
References 24 publications
1
97
0
Order By: Relevance
“…Unfortunately, the existence and significance of fCCE have been overlooked for a long time 11 12. As described recently,4 we proposed that AE were classified two main groups: AE including CCs, fibrin, red blood cells, macrophages and calcification; and fCCE including only CCs. The former will rapidly cause much more larger infarcts that are visible on imaging, such as CT, MRI and optical coherence tomography, rather than the latter; the latter will very slowly cause small or tiny infarcts that will not be recognised only on imaging studies, during the clinical course, or on histological examination.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Unfortunately, the existence and significance of fCCE have been overlooked for a long time 11 12. As described recently,4 we proposed that AE were classified two main groups: AE including CCs, fibrin, red blood cells, macrophages and calcification; and fCCE including only CCs. The former will rapidly cause much more larger infarcts that are visible on imaging, such as CT, MRI and optical coherence tomography, rather than the latter; the latter will very slowly cause small or tiny infarcts that will not be recognised only on imaging studies, during the clinical course, or on histological examination.…”
Section: Discussionmentioning
confidence: 97%
“…Although atheromatous emboli (AE), including cholesterol crystals (CCs), fibrin, macrophages and calcification, are released into coronary circulation during percutaneous coronary intervention (PCI) in acute coronary syndrome (ACS),1–3 AE are divided into two main groups: classic AE and free cholesterol crystal emboli (fCCE) 4. The number of released fCCE and their role in ACS have not been documented yet.…”
Section: Introductionmentioning
confidence: 99%
“…Recently ruptured aortic plaques, which might cause atheromatous embolization, are thought to be not mainly iatrogenic, but spontaneous and continuously ongoing. Komatsu et al showed that spontaneous ruptured aortic plaques (SRAP) are present in about 86.4% of patients who were suspected to have stable angina with no aneurysms, using nonobstructive angioscopy (NOA) [22]. Therefore, in patients with aneurysms with increased number of thrombi, NOA might help to identify a greater number of SRAP.…”
Section: Discussionmentioning
confidence: 99%
“…11 Recently, Komatsu et al observed the aortic wall on angioscopy in 324 patients with suspected coronary artery disease (CAD). 12 They found spontaneous ruptured aortic plaque in 262 patients (80.9%), of whom 120 patients had plaque rupture below the diaphragm portion of the aorta (Figure 1). 12 Figure 2 shows representative angioscopy of the descending aorta of our case.…”
mentioning
confidence: 99%
“…12 They found spontaneous ruptured aortic plaque in 262 patients (80.9%), of whom 120 patients had plaque rupture below the diaphragm portion of the aorta (Figure 1). 12 Figure 2 shows representative angioscopy of the descending aorta of our case. Ruptured plaque, subintimal bleeding and cholesterol crystal were observed in the infrarenal aorta but the vulnerability was lower in the suprarenal aorta.…”
mentioning
confidence: 99%